The distress call of Caiman crocodilus crocodilus (Crocodylia: Alligatoridae) in western Amazonia, Brazil - Roberto, Igor Joventino; Botero-Arias, Robinson (Zootaxa, 2013)
Analysis of vocalization can play a significant role in taxonomic studies, helping to identity cryptic species in species complex, as has been show for different vertebrate groups: primates (Zimmermann 1990), birds (Alström & Ranft 2003), amphibians (Padial & De La Riva 2009). In reptiles the analysis of vocalization has been explored mostly in behavioral, ecological, morphological and physiological studies, especially in lizards (Gans 1973; Frankenberg & Werner 1992; Russel et al. 2000) and crocodilians (Herzog & Burghardt 1977; Vergne et al. 2009). However crocodilians have the most complex acoustic repertoire, especially during the early stages of their life (Vergne et al. 2009), having different functions according to their stimulus and being classified as hatching, contact, annoyance, threat and distress calls (Britton 2001).